A History of the Pakistan Army : Wars and Insurrections - Cloughley, Brian (Karachi Oxford University Press, 2014)
The scope of this in-depth study of the Pakistan Army is wide as the army has played a major part in the country's history. The author describes Pakistan's violent internal politics and erratic international relations with deep knowledge gained through long association with the country and its armed forces. Pakistan's wars with India are covered vividly, drawing on unpublished material and details from Indian as well as Pakistani sources. The country's resurrection under Zulfikar Ali Bhutto is described, as is the decade of dictatorship that followed his period in power. The story of its aftermath, when Pakistan grappled with unaccustomed democracy and verged on anarchy, is told with the aid of personal knowledge of many of the senior players. This fourth edition incorporates new chapters covering the Musharraf years, the effects on Pakistan of the war in Afghanistan and operations in the border region, the nuclear programme, relations with the US, and discussion of the Directorate of Inter-Services Intelligence.
Include Maps, Tables, Graphs and Index.
Keywords: Pakistan -- Politics and government -- Pakistan. Army